Study Of The Carrying Capacity Of The Tutud Lake, Tombatu, South-East Minahasa, For Aquaculture Production, Using [P] Parameter - Firamitha Suban; Indra R.N. Salindeho; Novie P. L. Pangemanan (Jurnal Ilmiah PLATAX, 2019)
The research is aimed to assess the carrying capacity of the Tutud Lake waters,  to ensure a sustainable aquacutural production.  The carrying capacity of the Tutud lake was assessed using the method developed by Beveridge (2004), where several parameters of water quality, aquacultural production, and the physical condition of the lake physic  such as, the dimensions of the Lake, flushing rate, total phosphate [P], total aquacultural production per year and Food Conversion Ratio (FCR), were required in the assessment. Collected data were, then, analyzed using the procedures of calculation, which were combined with the several assumptions and modeling based on the previous research (Beveridge, 2004).  Water sample  for phosphate [P] analysis were collected four times with an interval of 7 days, and undertaken at four different positions which  representing the overall water condition of the lake.  Ammonia, Nitrite and Nitrate content of the waters were measured twice with an interval of 1 month.  Daily fluctuation measurements were undertaken for DO, pH and temperature.  Aquacultural protocols and production data were collected using questionnaire and by direct observation at the farm. The result shows that the average phosphate [P] content of the waters of Tutud lake is as high as 1,068 mg/L, which surpasses the maximum recommended value for waters used for aquacultural production.  DO is at the range of 2,2 – 5,0 mg/L, while temperature ranges from 25,3oC to 29oC, and  pH value varies between 6,38 and 7,89.  Average Nitrite content, 0,004mg/L, and Nitrate content,  4,51mg/L, of the waters of  Tutud Lake are at the safe level for aquaculture.  On the contrary, Ammonia content, 0,34mg/L, and H2S content, 0,681mg/L, of the Lake are at the insecure level for aquaculture animals.  Total aquacultural production per year in Tutud Lake , around 22,5 tons of fish per year, is also surpasses the carrying capacity of the waters of the Tutud  Lake which is only as high as 21,48tonnes.  Hence, the total production for the coming year must be reduced as many as 1,02 tones.Keywords: carrying capacity, water quality, production, Lake Tutud, TombatuABSTRAKPenelitian ini bertujuan untuk mengetahui kapasitas produksi optimal untuk menunjang aktivitas akuakultur yang berkelanjutan di danau Tutud dengan menggunakan parameter fosfor. Penelitian dilakukan di danau Tutud, Tombatu, Minahasa Tenggara, selama tiga bulan yang dimulai dari bulan September 2018 sampai bulan Januari 2019. Penentuan daya dukung untuk menunjang aktivitas akuakultur di danau Tutud menggunakan metode yang diberikan oleh Beveridge (2004), dimana dalam tahapan-tahapan prosedur penentuan daya dukung diperlukan sejumlah data menyangkut kondisi fisik danau, kandungan fosfor [P] perairan, tingkat pergantian air danau (flushing rate), produksi ikan total per tahun serta data operasional akuakultur seperti jenis pakan, jumlah pakan dan FCR. Data tersebut kemudian dianalisis menggunakan tahapan-tahapan kalkulasi yang dikombinasikan dengan beberapa asumsi hasil pemodelan penelitian sebelumnya (Beveridge, 2004). Pengambilan sampel untuk pengukuran fosfor dilakukan empat kali selama penelitian, pada empat titik yang mewakili keseluruhan danau, yaitu lokasi di dekat inlet (titik I), diluar lokasi KJT (titik II), di lokasi KJT (titik III) dan di dekat outlet (titik IV). Pengukuran fluktuasi harian dilakukan untuk parameter kualitas air DO, pH, suhu, sementara amoniak, nitrit, nitrat dan H 2 S diukur dua kali selama penelitian. Data operasional dan produksi akuakultur dikumpulkan menggunakan kuesioner serta observasi langsung.Hasil penelitian menunjukkan rataan kandungan fosfat parairan danau Tutud adalah 1,068 mg/l, sudah melewati batas maksimum baku mutu kualitas air untuk akuakultur. Hasil pengukuran untuk beberapa parameter kualitas air lainnya: DO berada pada kisaran 2,2 – 5,0 mg/l, suhu berada pada kisaran 25,30 0 C – 29 0 C, pH berada pada kisaran 6,38 – 7,89, rataan kandungan amoniak 0,34 mg/l, nitrit 0,004 mg/l , nitrat 4,51 mg/l, serta H 2 S 0,681 mg/l. Total produksi ikan per tahun di danau Tutud, sebesar 22,5 ton, sudah melebihi daya dukung perairan danau Tutud. Hasil analisis daya dukung perairan menurut Beveridge (2004), produksi akuakultur di danau Tutud harus diturunkan sebesar 1,02 ton untuk produksi tahun ke depan.Kata kunci: daya dukung, kualitas air, Produksi, Danau Tutud, Tombatu